The impact of national culture on the management of work teams in Chile - Raineri B., Andrés (Estudios de Administración, 2003)
It has been shown that the management of work teams is dependent on the culture where these are being developed. This research analyzes the perceptions that have a sample of chilean workers about the culture where they work and discusses the consequences of these perceptions for the development of work teams under such culture. In a first section of this paper new categories are developed in order to describe work culture in Chile. In a second section, using sample of 1008 subjects, the preferences of the subjects for these and other descriptors were analyzed. Results show that work culture in Chile can be described as being characterized by: individualism, paternalism, conflict avoidance, authoritarianism, improvisation, and classism. The implications and limitations of the methodology used in this study are discussed. The similarities and differences with other Chilean work culture research and essays are also analyzed. Finally, the consequences of these results, for the development of work teams in such a culture, are further developed.